(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The article seeks to investigate, by means of the French line discourse analysis method, how the discursive approach about no gender fashion is made in the magazine Vogue Brasil, considering, for this purpose, the editions aired in the period from January to June 2020, in which there are five approaches to the subject, divided into three subjects and two editorials. It is worth noting that Vogue Brasil is today the only print title specialized in fashion in Brazil to circulate monthly. Stands out in the production of articles, columns and editorials on the national and international fashion scene and is associated with hegemonic and dominant discursive structures of fashion, following the speeches themselves headed by major brands, among them, that of the no gender fashion, that has been attracting the attention of creators since 2015. In spite of the coverage of the event being present in the pages of Vogue Brasil we see, thus, that the publication does not depart from a pattern of fashion coverage that accompanies it since its origin in Brazil and that may be related to the maintenance of a status quo that legitimizes power relations still dominant in the relationship between gender and clothing in the fashion scene national.